Raman Spectroscopy of Bacterial Species and Strains Cultivated under Reproducible Conditions. Issue 5 (11th July 2012) - Almarashi Almarashi, Jamal F. M. Jamal F. M.; Kapel Kapel, Natalia Natalia; Wilkinson Wilkinson, Thomas S. Thomas S.; Telle Telle, Helmut H. Helmut H.
Abstract : Rapid and reproducible discrimination between bacterial pathogens is a clear goal in microbiological laboratories when processing infected clinical samples. In this study Raman spectra were taken from at least 30 colonies of four strains of bacteria including Staphylococcus epidermidis (1457 and 9142) and Escherichia coli (K12 and Top 10) using the Renishaw in Via Raman microscope system. Analysis based on principal components suggests that even strain differentiation (e.g., 1457 versus 9142 or K12 versus Top10) is possible.